Adapting transformation and transforming adaptation to climate change using a pathways approach. Issue 124 (October 2021) - Colloff, Matthew J.; Gorddard, Russell; Abel, Nick; Locatelli, Bruno; Wyborn, Carina; Butler, James R.A.; Lavorel, Sandra; van Kerkhoff, Lorrae; Meharg, Seona; Múnera-Roldán, Claudia; Bruley, Enora; Fedele, Giacomo; et al.
Highlights: There is a clear need to shift to intentional transformative adaptation (ITA). ITA can be achieved through incremental and transformative actions. Central to ITA are issues of social change and power imbalances. Participants in six case studies could overcome some challenges to implementing ITA. Enabling change requires pluralism, knowledge contestation, and re-politicisation. Abstract: Human actions have driven earth systems close to irreversible and profound change. The need to shift towards intentional transformative adaptation (ITA) is clear. Using case studies from the Transformative Adaptation Research Alliance (TARA), we explore ITA as a way of thinking and acting that is transformative in concept and objectives, but achieved through a mix of incremental and transformative co-production processes that ultimately lead to the social-ecological system being transformed. Central to ITA are social and political issues of how individuals and collectives address environmental and social change and deal with power imbalances. ITA approaches are claimed to help overcome adaptation challenges, including: 1) re-framing human-nature relationships; 2) dealing with uncertainty; 3) engendering empowerment and agency and 4) addressing conflicting values and interests. However, it is unclear if these approaches work in practice. We examined six adaptation case studies in which participants used processes of: 1) co-producing visions of the future; 2) re-framing values, rules and knowledge to shift decision contexts for adaptation and 3) implementing actions using theories of change and adaptation pathways. We assessed the extent to which participants could use these processes to address their adaptation challenges. We found evidence of many positive achievements towards the implementation of ITA, but also examples where processes were not working, such as communities having difficulties in finding ways to work co-operatively. Different processes will be needed to address these issues, such as promoting pluralism, knowledge contestation, and deliberative re-politicisation of the adaptation agenda to shift power imbalances and enable change.